2021
DOI: 10.3390/s21134589
|View full text |Cite
|
Sign up to set email alerts
|

A Method of Codec Comparison and Selection for Good Quality Video Transmission Over Limited-Bandwidth Networks

Abstract: Finding a proper balance between video quality and the required bandwidth is an important issue, especially in networks of limited capacity. The problem of comparing the efficiency of video codecs and choosing the most suitable one in a specific situation has become very important. This paper proposes a method of comparing video codecs while also taking into account objective quality assessment metrics. The author shows the process of preparing video footage, assessing its quality, determining the rate–distort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Striking a balance between video quality and bandwidth requirements is critical for any compression method, and the added quality metrics will also support further relevant studies, as shown as an example by a recent work [63].…”
Section: Data Compression and Objective Quality Assessment Methodologymentioning
confidence: 75%
“…Striking a balance between video quality and bandwidth requirements is critical for any compression method, and the added quality metrics will also support further relevant studies, as shown as an example by a recent work [63].…”
Section: Data Compression and Objective Quality Assessment Methodologymentioning
confidence: 75%
“…In today's marine operations, video transmission has become the mainstream [1]. Underwater video transmission can improve the efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…High data volumes, especially for multimedia content such as videos or high-resolution images, can strain network infrastructure and result in slow or unreliable data transfer. Processing and rendering digital media content can consume significant energy, leading to reduced device runtime, while resource-constrained devices may struggle with the processing power required to efficiently encode or decode high-resolution or high-bitrate video, audio, or imaging formats [2,3].…”
Section: Introductionmentioning
confidence: 99%